Human alveolar echinococcosis in Slovakia: Epidemiology and genetic diversity of Echinococcus multilocularis, 2000-2023. - Daniela Antolová; Viliam Šnábel; Júlia Jarošová; Serena Cavallero; Stefano D'Amelio; Yaroslav Syrota; Róbert Rosoľanka; Mária Avdičová; Martina Miterpáková (Public Library of Science (PLoS), 2024)
Human alveolar echinococcosis (AE) is a serious parasitic disease caused by larval stages of Echinococcus multilocularis. Between January 2000 and October 2023, 137 AE cases were confirmed in Slovakia. The average annual incidence increased from 0.031 per 100,000 inhabitants between 2000 and 2011, to an average of 0.187 since 2012, i.e. about six times. Among patients, 45.3% were men and 54.7% were women; the mean age at the time of diagnosis was 52.8 years. Most cases were diagnosed in the age groups 51-60 years and 61-70 years (33 cases each), and eight patients fell into the age category ≤ 20 years. To better recognize the gene diversity in clinical samples, metacestodes from 21 patients collected between 2013 and 2021 were subjected to DNA sequencing of four mitochondrial genes. Using concatenated sequences of cob (603 bp), nad2 (882 bp) and cox1 (789 bp) gene fragments, 14 isolates (66.7%) were assigned to the European E5 profile of E. multilocularis, two isolates (9.5%) to the E5a subtype, four isolates (19%) to the E4 profile, and one isolate (4.8%) to haplogroup E1/E2. The E5-type profiles and E4 profiles were distributed throughout the country, whereas the E1/E2 profile was found in the patient from western Slovakia. According to the data obtained and GenBank sequences, the E5-type dispersal is so far limited to central-eastern Europe and the variant seems to be indigenous to that region. The admixture with the haplotypes E4 and E1/E2 could have taken place from a historical endemic focus during the fox expansion in the last decades. By employing the nad1 fragment, a typical European haplotype was observed in all 21 resolved Slovak samples. The acceleration in the AE incidence in the last decade suggests the emergence of the disease and the need for further research on human and animal isolates.